Development of Intelligent Indicators Based on Cellulose and Prunus domestica Extracted Anthocyanins for Monitoring the Freshness of Packaged Chicken - Mustafa Ahmed; Ipsheta Bose; null Nousheen; Swarup Roy (International Journal of Biomaterials)
Meat is a widely consumed food globally; however, variations in storage conditions along its supply chain can pose a potential food safety risk for consumers. Addressing this concern, we have developed freshness indicators designed to monitor the condition of packaged chicken. In this study, anthocyanins were infused with cellulose paper measuring 2 × 2 cm, and subsequent analysis focused on examining color changes concerning deteriorating chicken stored at 30°C for 48 h, with varying sample sizes being considered. The rise in total volatile nitrogen (TVB-N) compounds from an initial value of 3.64 ± 0.39 mg/100 g to 28.17 ± 1.46 mg/100 g acted as the stimulus for the color change in the indicator, simultaneously influencing the pH from the initial 7.03 ± 0.16 to 8.12 ± 0.39. The microbial load (aerobic plate count) of the chicken samples was also significantly increased. This collective shift in various parameters strongly suggests the occurrence of spoilage in chicken meat. The pH indicators exhibited a dark pink to red color for fresh chicken. As the chicken meat turned towards spoilage, the indicators changed to a dark blue and then a pale green color. FTIR spectroscopy results confirmed the presence of cellulose and anthocyanins. The FTIR analysis also validated the immobilization of plum anthocyanins within the cellulose paper and assessed their stability after 8 months of storage. Notably, the indicators demonstrated rapid sensitivity, showing a 20.5% response within one minute of ammonia exposure, which further increased to 29.5% after 3 min of exposure. The total color difference (ΔE) steadily rose in all the examined samples and also under various storage conditions. Overall, the indicators developed in this study exhibited a highly pronounced color transition, capable of distinguishing between fresh and spoiled chicken samples depending on the extent of spoilage and the specific day of observation.